Expression of HIV-1 Vpu leads to loss of the viral restriction factor CD317/Tetherin from lipid rafts and its enhanced lysosomal degradation. - Ruth Rollason; Katie Dunstan; Peter G Billcliff; Paul Bishop; Paul Gleeson; Helen Wise; Paul Digard; George Banting (PLoS ONE)
CD317/tetherin (aka BST2 or HM1.24 antigen) is an interferon inducible membrane protein present in regions of the lipid bilayer enriched in sphingolipids and cholesterol (often termed lipid rafts). It has been implicated in an eclectic mix of cellular processes including, most notably, the retention of fully formed viral particles at the surface of cells infected with HIV and other enveloped viruses. Expression of the HIV viral accessory protein Vpu has been shown to lead to intracellular sequestration and degradation of tetherin, thereby counteracting the inhibition of viral release. There is evidence that tetherin interacts directly with Vpu, but it remains unclear where in the cell this interaction occurs or if Vpu expression affects the lipid raft localisation of tetherin. We have addressed these points using biochemical and cell imaging approaches focused on endogenous rather than ectopically over-expressed tetherin. We find i) no evidence for an interaction between Vpu and endogenous tetherin at the cell surface, ii) the vast majority of endogenous tetherin that is at the cell surface in control cells is in lipid rafts, iii) internalised tetherin is present in non-raft fractions, iv) expression of Vpu in cells expressing endogenous tetherin leads to the loss of tetherin from lipid rafts, v) internalised tetherin enters early endosomes, and late endosomes, in both control cells and cells expressing Vpu, but the proportion of tetherin molecules destined for degradation rather than recycling is increased in cells expressing Vpu vi) lysosomes are the primary site for degradation of endogenous tetherin in cells expressing Vpu. Our studies underlie the importance of studying endogenous tetherin and let us propose a model in which Vpu intercepts newly internalised tetherin and diverts it for lysosomal destruction rather than recycling to the cell surface.